Breast Cancer Phenotype Associated With Li-Fraumeni Syndrome: A Brazilian Cohort Enriched by TP53 p.R337H Carriers - Sandoval, Renata Lazari; Polidorio, Natalia; Leite, Ana Carolina Rathsam; Cartaxo, Mariana; Pisani, Janina Pontes; Quirino, Carla Vanessa; Cezana, Loureno; Pereira, Natálya Gonçalves; Pereira, Allan Andresson Lima; Rossi, Benedito Mauro; Achatz, Maria Isabel (Frontiers in Oncology, 2022)
Breast cancer (BC) is the most prevalent malignancy in women with Li-Fraumeni syndrome (LFS). The literature on BC in LFS is limited due to its rarity worldwide. A TP53 founder pathogenic variant (c.1010G>A; p.R337H) is responsible for the higher prevalence of this syndrome among women of Brazilian ancestry. Purpose: The aim of the study was to describe the BC phenotype expressed by Brazilian female LFS carriers and compare the data between p.R337H and other TP53 germline pathogenic/likely pathogenic variants (non-p.R337H carriers). Methods: We searched for cases of TP53 germline pathogenic/likely pathogenic variant carriers affected by BC included between 2015 and 2020 in the BLiSS (Brazilian Li-Fraumeni Study) registry at the Sírio-Libanês Hospital. Results: Among 163 adult female carriers from the registry, 91 (56%) had received a BC diagnosis, including 72 p.R337H carriers. BC was the first cancer diagnosed in 90% of cases. Early onset BC (age ≤ 45 years) was diagnosed in 78.2% of cases (11.5% < 31 years; 66.7% 31–45 years; 21.8% > 45 years). The median age of BC diagnosis for p.R337H carriers was 39.5 years (range 20–69 years) compared to 34 years (range 21–63 years) for non-p.R337H carriers (p = 0.009). In total, 104 breast cancers were observed in 87 women. Bilateral BC was observed in 29.3% of cases. Histology was available for 96 tumors, comprising 69 invasive breast carcinomas, which were mostly invasive ductal carcinomas (95.6%), 25 ductal in situ carcinomas and 2 soft-tissue sarcomas. Overall, 89.2% of tumors were hormone receptor (HR)-positive, 41% were human epidermal growth factor receptor 2 (HER2)-positive, and 34.6% showed HR and HER2 co-expression. In addition, 55.4% of patients opted for contralateral prophylactic mastectomy after a first BC diagnosis. There were no significant differences in the risk of developing contralateral BC or in the immunohistochemical profile between p.R337H and non-p.R337H groups. Conclusions: The expressed phenotype of p.R337H is similar to that of other TP53 pathogenic/likely pathogenic variants, except for an average older age at the onset of disease; however, this is still younger than the general population.